Perancangan Aplikasi Penjadwalan Kegiatan Kepala Kantor Regional VI BKN Medan - Samsudin; Tamaulina Tama (Jurnal Ilmiah Sistem Informasi dan Teknik Informatika (JISTI), 2024)
The aim of this research is to perfect the computerized activity scheduling system at the State Civil Service Agency (BKN) Regional Bureau 6 Medan. The BKN Medan VI Regional Office which is responsible for the development and management of its ASN in the North Sumatra region often faces challenges in preparing agendas. Regional Head of Regional Head activities. In this context, a scheduling application is needed as a solution to increase the efficiency and accuracy of activity management plans. This research uses a prototype-based system development methodology which consists of five phases: Communication, Quick plan, Modeling Quick Design, Construction of Prototype and Deployment Delivery & Feedback. In addition, data collection was carried out through direct observation of BKN Medan Regional Office VI staff and literature review to support application design. It is hoped that the results of this research can provide important input for the planning of the Head of Regional Office and the Secretary of the Regional Office, overcome the problem of unexpected schedule changes, and facilitate presentations and related management. The implications of this research can provide a basis for developing applications within institutions.